2006
DOI: 10.1161/circulationaha.105.000851
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Administration of Metoprolol Is More Effective Than Oral Administration in the Prevention of Atrial Fibrillation After Cardiac Surgery

Abstract: Background-Atrial fibrillation (AF) is the most common arrhythmia to occur after cardiac surgery, with an incidence of 20% to 40%. AF is associated with postoperative complications, including increased risk of stroke and need of additional treatment, as well as prolonged hospital stay and increased costs. It has been shown that prophylactic oral administration of ␤-blocker therapy reduces the incidence of postoperative AF after cardiac surgery. However, it is possible that absorption of drugs is impaired after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 26 publications
2
46
0
Order By: Relevance
“…This finding is likely related to the fact that betablocker absorption is considerably reduced in the early postoperative period resulting in decreased bioavailability of orally administered preparations. 30 It has been previously shown that perioperative administration of beta-blockers is associated with higher stroke rates in both surgical and non-surgical patient populations. 18,31,32 Postoperative neurological complications can be related to both the cardiovascular and the central nervous system effects of beta-blockers.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is likely related to the fact that betablocker absorption is considerably reduced in the early postoperative period resulting in decreased bioavailability of orally administered preparations. 30 It has been previously shown that perioperative administration of beta-blockers is associated with higher stroke rates in both surgical and non-surgical patient populations. 18,31,32 Postoperative neurological complications can be related to both the cardiovascular and the central nervous system effects of beta-blockers.…”
Section: Discussionmentioning
confidence: 99%
“…Halonen et al, in an attempt to compare the intravenous with the oral use of metoprolol, randomized 240 patients who underwent first on pump CABG, aortic valve replacement or combined aortic valve replacement and CABG. 36 In both groups, the metoprolol administration was based on heart rate for a 48 hour period. POAF presented a significant decrease (p = 0.036) in intravenous group (16.8%) compared to oral group (28.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Halonen, et al reported that intravenous administration of metoprolol was more effective than oral administration for the prevention of atrial fibrillation, with the incidence being 28.1% in the oral group versus 16.8% in the intravenous group. 10) In contrast, Maniar, et al compared the prophylactic effect of intravenous esmolol with oral β-blockers and found no difference in the occurrence of POAF between the 2 groups, although hypotension was significantly more frequent in the intravenous esmolol group and this was a safety problem. 11) In a large-scale study comparing early intravenous administration with oral administration of metoprolol in 45852 patients after acute myocardial infarction, the incidence of non-fatal myocardial infarction and ventricular fibrillation was lower in the intravenous group than the oral group.…”
Section: Cause Of Atrial Fibrillation After Cardiac Surgerymentioning
confidence: 97%